1993
DOI: 10.1038/ki.1993.281
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular fibrinolytic activity in anti-GBM glomerulonephritis in rabbits

Abstract: Fibrin is an important mediator of injury in severe proliferative forms of glomerulonephritis (GN). Normal glomeruli express fibrinolytic activity, which may protect against the injurious effects of fibrin deposition. Changes in glomerular fibrinolytic activity (GFA) may play an important role in modulating fibrin accumulation in GN. To study the changes in GFA associated with fibrin deposition in GN, autologous phase anti-glomerular basement antibody initiated GN (anti-GBM GN) was studied in rabbits. Net GFA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 32 publications
0
35
2
Order By: Relevance
“…6 Upregulation of PAI-1 in diseased glomeruli has also been well documented in experimental immune complex-mediated glomerulonephritis 4,5,19,20 and in human glomerulonephritis 21 and was observed in the mesangium of TSLP transgenic mice. PAI-1 can be induced by TGF-␤1 in rodent kidneys and in cultured mesangial cells.…”
Section: Discussionmentioning
confidence: 99%
“…6 Upregulation of PAI-1 in diseased glomeruli has also been well documented in experimental immune complex-mediated glomerulonephritis 4,5,19,20 and in human glomerulonephritis 21 and was observed in the mesangium of TSLP transgenic mice. PAI-1 can be induced by TGF-␤1 in rodent kidneys and in cultured mesangial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Renal histology was assessed on tissue sections fixed in Bouin's fixative, stained with silver methenamine/trichrome. Other indices of injury at these time points in this model, including glomerular crescent formation, fibrin deposition, proteinuria, macrophage infiltration, tissue factor expression and changes in fibrinolytic activity have previously extensively characterized in this model (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…GFD was assessed in a blinded protocol. Only glomeruli cut in or near the equatorial cross section were included and the extent of immunofluorescence staining in glomeruli scored on a scale from 0 (normal) to ϩ 3 (fibrin deposition involving greater than two thirds of the glomerular cross section) as previously described (17,27,31). At least 50 glomeruli per animal were scored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Number of plasminogen activator inhibitors, such as protease nexin-1 (PN-1) and plasminogen activators inhibitor PAI-1, among their complex activities, they inhibit generation of plasmin. Several studies demonstrated decreased PA activity and plasmin activity in glomeruli in various forms of experimental injury that resulted in mesangial matrix expansion [52,53]. Increased levels of PAI-1 have been observed in various forms of kidney diseases leading to renal fibrosis [53,54].…”
Section: Growth Factors and Other Regulators Of Renal Fibrosing Injurymentioning
confidence: 99%